Ferroelectric-gate carbon nanotube field effect transistor for non-volatile memory application - Cheah, Jason Jun Wei (2014)
Carbon nanotube field effect transistor has attracted much attention and is a promising candidate for next generation nanoelectronics. Significant hysteresis usually exists in its transfer characteristics between the forward and reverse gate bias sweeps, which is problematic for application in logic devices. This behavior is due to a charge injection process at the carbon nanotube-dielectric interface and has been suggested to serve for nonvolatile memory applications. However, the charge injection process is highly susceptible to environmental changes and has a large charge injection surface, in the range of a few um. In this project, we explore the possibility of using ferroelectric materials as the gate dielectric of a carbon nanotube network transistor. The spontaneous polarization of ferroelectric materials offers stability and controllability of the surface charge.